Utilization of Instagram as a Digital-Based Communication Media in Reading Japanese Stories - Hasibuan, Annalisa Sonaria; Nasution, Laraiba (Universitas Harapan Medan, 2023)
In the era of growing social media, Instagram is one of the platforms that can be utilized to facilitate interactive foreign language learning. The purpose of this study is to utilize Instagram as a digital-based social media in reading stories using Japanese so that it is expected that students can be more active, brave and expressive in reading so that the content of the story can be conveyed properly, students can also be more creative in making interesting videos by utilizing the many features contained in Instagram. This research method adopted a descriptive qualitative approach involving 22 students. Students were given texts in Japanese writing, chose one of the texts to study which then had to be read out in the form of a video that was uploaded to each student's Instagram account according to the conditions that had been given. Research data were collected through participant observation, questionnaires, and analysis of the results of the tasks uploaded to Instagram. The results showed that learning to read Japanese stories on Instagram provides benefits in the development of reading skills. Students demonstrated comprehension of the text in their target language. There was also high motivation and satisfaction with the Instagram learning experience. This study provides insight into the potential of Instagram as one of the learning media in reading Japanese stories.